Governance in the pandemic: science as moral regulation and the problems of biopolitics (Simbiótica. Revista Eletrônica, 2020)
The purpose of the article is to think about one of the most important issues regarding the pandemic: the complexity of the disputes over its governance. For this, we approached a set of texts written in the heat of the moment, by philosophers and sociologists who faced the challenge of thinking, in a situation of full uncertainty and unpredictability, the social, political, cultural and even epistemic consequences of the pandemic. For this, we divided the article into three parts that interpenetrate: science as moral regulation, the problems of biopolitics and Globalization and informatization of society.Keywords: Pandemic; science; biopolitics; informatization.